Compatibility of hypokalaemia caused by low-dose prednisolone plus abiraterone acetate therapy for metastatic castration-resistant prostate cancer - Shota Torii; Aya Torii-Goto; Tamaki Tanizawa; Takashi Sakakibara; Ryosuke Oguri; Haruka Nagase; Yuri Nakao; Tomoyuki Hirashita; Kuniaki Tanaka; Norio Takimoto; Takahiro Hayashi (Journal of Pharmaceutical Health Care and Sciences)
Abstract Background This study aimed to investigate the relationship between low-dose prednisolone (PSL) and the incidence of hypokalaemia at abiraterone acetate (abiraterone) plus PSL combination therapy targeting Japanese patients with metastatic castration-resistant prostate cancer (mCRPC). Methods This retrospective observational study included 153 Japanese patients treated with abiraterone and PSL for mCRPC at Kariya Toyota General Hospital and Gifu General Medical Center between September 2014 and October 2022. The incidence of grade ≥ 2 hypokalaemia as well as serum potassium level variations and the continuous combination therapy duration were compared between the low-dose (5 mg/day of PSL) and the standard-dose (10 mg/day of PSL) groups. Results This study included 153 patient of which 95 were matched to establish the analysis population. The low-dose and the standard-dose groups consisted of 13 and 82 patients, respectively. No significant difference in the incidence of grade ≥ 2 hypokalaemia was observed between the two groups [15.4% (2/13 patients) in the low-dose group and 12.2% (10/82 patients) in the standard-dose group, P = 0.667]. The low-dose group exhibited a decrease in serum potassium levels from 4.63 on day − 7 − 0 to 4.16 mmol/L on day 84 ± 10 (n = 7, P = 0.066), and serum potassium levels from day − 7 − 0 to 84 ± 10 in the low-dose group appeared to be great in the standard-dose group (n = 37, P = 0.475). The Kaplan–Meier curves for continuity of abiraterone and PSL therapy were not significantly different between the low-dose group (n = 13) and standard-dose group (n = 82, P = 0.427). Conclusion Combination therapy with abiraterone and 5 mg/day of PSL in Japanese patients with mCRPC did not change the incidence of grade ≥ 2 hypokalaemia. However, although not significant, 5 mg/day of PSL demonstrated a decreasing trend in serum potassium levels with a larger degree of change than that of 10 mg/day of PSL. Therefore, the combination of abiraterone and 5 mg/day PSL can be administered to Japanese patients with mCRPC. The patients must be monitored for hypokalaemia through measurement of serum potassium levels and observation of subjective symptoms such as muscle weakness, convulsion etc. In addition, the doctor or the pharmacist must explain these symptoms to the patient and instruct them to consult their medical staff immediately in the event of development of such symptoms.